Biofertilizer use associated with different forms of planting in the development of the initial coffee arabic - Figueiredo, Lucas Henrique; Miranda, Gustavo Rabelo Botrel; Faria Vilella, Paulo Marcio (Coffee Science - ISSN 1984-3909, 2017)
The objective was to evaluate the vegetative development, productivity and income of the coffee the course of the seasons 2014/2015 and 2015/2016 deployed in cropping systems in the pit, planting in no-till and conventional tillage and evaluate the coffee yield of the biennial during the two years, planting systems have been associated with the use or not of liquid organic foliar fertilizer, and, as a parameter we evaluated plant height, stem diameter, crown diameter, number of reproductive branches as vegetative development; crop yields, production and biennial performance, and as a resulted there was no statistical difference in performance between the types of planting and the application of biological fertilizer foliar, for the harvest of 2014/2015 and 2015/2016; was no statistical difference for the type of planting which the pits excelled the other; for coffee yield of biennial planting that best suited was the grooves.